Solitary Fibrous Tumor of the Paraspinal Region: A Case Report - Bhandari, Rajeev; Bista, Prakash; Jha, Rajiv; Shrestha, Rajendra; Khambu, Bikesh (Nepal Journal of Neuroscience, 2018)
Solitary fibrous tumor (SFT) is a rare neoplasm occurring in the central nervous system. It rarely occurs in the spine. SFTs represent a wide range of neoplasm's, ranging from benign to malignant. This case reports on a 51 year- old male with localized solitary fibrous tumor on left para spinal region which was observed by Magnetic Resonance Imaging. Patient complained a low back pain radiating to left lower limb for successive 10 days. Laboratory investigation such as CBC and renal function test was normal. A Confirmation of patients Solitary fibrous tumor (SFT) was done on the basis of surgical, radiological, histological and immunohisto chemical findings.